Effects of Aeration Treatment on γ-Aminobutyric Acid Accumulation in Germinated Tartary Buckwheat (Fagopyrum tataricum). (21st June 2016) - Guo, Yuanxin; Zhu, Yunhui; Chen, Chunxu; Chen, Xiaoman
Abstract : To explore the optimum condition of γ -aminobutyric acid (GABA) accumulation in germinated tartary buckwheat, effects of some factors including aeration treatment, physiological indexes, air flow rate, culture temperature, and pH value of cultivating solution under hypoxia on GABA in germinated tartary buckwheat were investigated. The results showed that the dark cultures with distilled water at 30°C, 2 days, and aeration stress with 1.0 L/min air flow rate at 30°C were optimal for GABA accumulation. Under these conditions, the predicted content of GABA was up to 371.98 μ g/g DW. The analysis of correlation indicated that there was a significant correlation (P < 0.01 ) between GABA accumulation and physiological indexes. Box-Behnken experimental analysis revealed that optimal conditions with aeration treatment for GABA accumulation in germinated tartary buckwheat were air flow rate of 1.04 L/min, culture temperature of 31.25°C, and a pH value of 4.21. Under these conditions, the GABA content was predicted as high as 386.20 μ g/g DW, which was close to the measured value (379 . 00 ± 9.30 μ g/g DW). The variance analysis and validation test suggested that this established regression model could predict GABA accumulation in tartary buckwheat during germination.